METODE SERVQUAL DAN QFD DALAM MEMPERBAIKIN KUALITAS PELAYANAN PADA TOKO SEPATU WEST STORE MEDAN - Uun Novalia Harahap; Yetti Meuthia Hasibuan; Rini Halila Nasution (Jurnal Abdi Ilmu, 2019)
In business disciplines, among others, production, sales, supply of goods, and services are the main factors in doing business, especially for customers. If a company creates things that can be handled and can be seen in a tangible form, then these services have no form but can be felt by customers. This should not be underestimated by business people, especially if the company is engaged in the service sector. In a service provider manufacturing business, quality is one of the various elements that must be considered, if the business has a competitive nature against competitors. Quality is considered crucial because it proves the product being sold, not only assessing the use or service, but also the suitability between the buyer and the user in utilizing the goods or services provided and selected. If the products and services offered have quality, then the level of consumer desire will also increase, this is called the provision of good service quality (Servqual). This research is a quantitative study using the Servqual and QFD (Quality Function Deployment) methods. This research was conducted by the authors at the West Store Medan Shoe Store, with the aim of knowing and analyzing the level of customer satisfaction with the quality of service and goods at the West Store Medan store. In this study, the authors carried out a description of each method, the aim was that the validity of the data produced would not be doubted. This research shows that there is still a lack of service at the West Store Medan Shoe Store, including the lack of agility of store employees in responding to buyers, lack of responsibility when serving, insufficient parking and cleanliness, and lack of complete facilities. Keywords: Klinik; BPJS; Quality Function Deployment (QFD; House of Quality (HOQ)